The People's Republic of China : Financial Sector Assessment Program; Anti-Money Laundering and Combating the Financing of Terrorism (AML/CFT)-Technical Note. (IMF Staff Country Reports; Country Report, 2018)
This Technical Note discusses the findings and recommendations made in the Financial Sector Assessment Program for China in the areas of Anti-Money Laundering and Combating the Financing of Terrorism (AML/CFT). The Chinese authorities have taken significant measures to enhance the AML/CFT legislative and regulatory framework since the 2007 Mutual Evaluation Report and have continued after the completion of the 2012 Mutual Evaluation follow-up report to take additional steps to bring the AML/CFT regime in line with the revised Financial Action Task Force standard. Continuing to implement these initiatives will strengthen the AML/CFT regime going forward. The authorities should also prioritize the completion of the National Risk Assessment.